PENERAPAN PENDIDIKAN KARAKTER BAGI MAHASISWA MELALUI KEARIFAN BUDAYA LOKAL DI UNIVERSITAS PANCASAKTI - Beni Habibi; A. Rony Yulianto (Universitas Muhammadiyah Semarang, 2018)
His study aims to determine: 1) the application of character education through local cultural wisdom among students, 2) supporting factors and inhibitors of character education through local cultural wisdom of students, 3) the results of the application of local culture-based character education to students. This research is a qualitative descriptive study of the research location at Pancasakti Tegal University using primary data sources and skuder namely data analysis techniques used by interviews and documentation. Data analysis is qualitative analysis. The results of this study indicate that, the application of character education through local cultural wisdom (case studies on Pancasakti Tegal University students include: 1. Application of character education in the learning or intracurecular process, namely a). fear of violating campus rules,b). lecturer commitment to students, c). the integrity of the lecturer honesty in the campus. 2. Application of character education through the student activity unit namely. a) art field, b) moral and community development. 3. Supporting Factors and Companions The application of character education through local cultural wisdom includes: supporting actors namely. A) factors of lecturer adherence, b). exemplary parents, c). exemplary community leaders, d). habituation factor. 4 inhibiting factors are a). technological advances such as mobile phones and TV, b) lack of communication between lecturers and parents. 5. The results of the application of character education through local culture are: a. students have not been disciplined b. students don't respect lecturers. Keywords: Character Education, Local Cultural Wisdom, Students